Community Empowerment Through Android-Based Herbal Plant Education Application Training for Traditional Medicine Information Access - Marsyah Marsyah; Vivek Sharma; Shadi Kedah (Jurnal Abdimas Cendekiawan Indonesia, 2026)
Limited public access to accurate information about herbal plants remains a barrier to the proper use of traditional medicine. Some communities still rely on inherited knowledge that is not always accompanied by scientific information regarding the benefits, processing methods, dosages, and potential side effects of medicinal plants. This community service activity aims to improve access to information on traditional medicine by training and mentoring participants in using an Android-based herbal plant education application. The activity partners are communities in Makassar City, around herbal cultivation sites, who still use medicinal plants in their daily lives. The implementation method includes identifying partner needs, compiling educational content, developing an Android-based application using an Agile approach, providing application training, mentoring, and evaluating through functional testing and user questionnaires. The introduced application has key features, including a list of herbal plants, information on benefits and processing methods, an image-based plant scanner, educational videos, and details on cultivation locations. Black Box testing results indicate that all application features operate as designed. An evaluation of 15 respondents showed a feasibility level of 88.2%, categorized as very feasible. The results of the activity indicate that this application can serve as a digital educational tool, helping the public access information about herbal plants in an easier, more engaging, and more structured way. Furthermore, training and mentoring help the public use the application's features more effectively. Therefore, this application has the potential to support public access to more structured, easily understood information about herbal plants.